Promoting Moral Growth: From Piaget to Kohlberg - Thomas J. Buttery (Educational Considerations, 1982)
A review of Promoting Moral Growth: From Piaget to Kohlberg by Richard H. Hersh, Diana P. Paolitto and Joseph Reimer.